Discovering the Secret Listener: Western Radio Broadcasts to Soviet Lithuania - Arlauskaitė Zakšauskienė, Inga (Lietuvos istorijos studijos, 2019)
The research of Western radio audiences in the Soviet Union was carried out by the department of Soviet Area Audience and Opinion Research, which was in charge of the RFE/RL; however, factual surveys were conducted by independent research institutes, which ensured that the results were neutral and no prejudices with regard to a particular broadcaster were present. The key indices to be measured were the size of the audience that listened to Western radio broadcasts as well as the listeners’ behavioral patterns. Making use of these parameters, the authorities of these radios were able to modify the character of radio programming, to design the content of the information provided, and to observe the potential influence of radio broadcasts in the context of ideological opposition. It is important to stress that based on the methodology and the amount of information available at that time, individual persons’ surveys conducted by Radio Liberty audience and the opinion research department were not adequate to what is considered, in the contemporary sense, proper public opinion research.